The impact of Internet finance on commercial banks' risk taking: Evidence from China - Pin Guo; Yue Shen (China Finance and Economic Review, 2016)
Background: Internet finance has grown rapidly in China over the past years. Through introducing internet finance's 'reducing management cost' and 'raising capital cost' effects into bank risk-taking model, this paper systematically investigates the dynamic and heterogeneous influence of internet finance on China commercial banks' risk-taking. Methods: Using internet finance index based on 'text mining' and data of 36 commercial banks from 2003 to 2013, we makes an SYS-GMM test. Results: The results show, firstly, the impact of internet finance on China commercial banks' risk-taking is a 'U' trend. The initial development of internet finance can help commercial banks to reduce management cost and risk-taking, but then internet finance will raise capital cost, and turn to exacerbate banks' risk-taking. Secondly, the response of China commercial banks' risk-taking is heterogeneous. Large commercial banks' response is slow, while small and medium banks' response is relatively sensitive. Conclusions: The conclusion showed the complexity of the implication mechanism and functional process of how internet finance affected China commercial banks' risk-taking.
Keywords: E44; G21; G29; 330; Internet finance; Commercial bank risk taking; System GMM estimation